Optimal design of step – cone pulley problem using the bees algorithm - Yusof, Noor Jazilah; Kamaruddin, Shafie (Springer Nature Singapore Pte Ltd, 2021)
Nowadays, there is a lot of optimization algorithms available to find an optimal solution in engineering problems. Most of these algorithms were developed based on the collective behavior of social swarms of ants, bees, a flock of birds, and schools of fish. It is commonly known as Swarm Intelligence (SI). Examples of algorithm categorized under SI are Particle Swarm Optimization (PSO), Ant Colony Optimization (ACO), and the Bees Algorithm (BA). The Bees Algorithm is considered one of the recent optimization algorithms and it has been successfully solved various types of problems. It is inspired by the food foraging behavior of honeybees in nature. This study applies the Bees Algorithm to minimize the weight of the stepped-cone pulley in its design and satisfy the constraints. The Bees Algorithm is used in this study to find the optimum solution for stepped-cone pulley design and found better results compared to other optimization algorithms.